Budilovsky, Agnes (audio interview #1 of 1) - Budilovsky, Agnes (b. 05/03/1899 - d. unknown); Feichtinger, Kris, interviewer
INTERVIEW DESCRIPTION</ - The first two interviews with Agnes Budilovksy were conducted jointly with Rose Falk; this is the first one conducted solely with Agnes. Like the other interviews, it was recorded at the ACWA union hall as part of a project on women in the union, particularly on those who were involved with the Chicago Women's Local. It was conducted by Kris Feichtinger, in cooperation with the Feminist History Research Project. Fall 1974